2017
DOI: 10.3847/1538-4357/834/1/91
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Column Density Tracers With Gamma-Ray Observations of the Ρ Ophiuchi Molecular Cloud

Abstract: Diffuse gamma-ray emission from interstellar clouds results largely from cosmic ray (CR) proton collisions with ambient gas, regardless of the gas state, temperature, or dust properties of the cloud. The interstellar medium is predominantly transparent to both CRs and gamma-rays, so GeV emission is a unique probe of the total gas column density. The gamma-ray emissivity of a cloud of known column density is then a measure of the impinging CR population and may be used to map the kpc-scale CR distribution in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…We note that all of the new extended sources are found at low latitudes (     | | b 4 20 ), 69 implying potential Galactic origin. We found the sources were generally associated with either SNRs or SFRs, the two exceptions being the ρ Oph Cloud, which was originally discovered by COSB at γ-ray energies (Mayer-Hasselwander et al 1980) and was previously found as an extended object in γ-rays (Lande et al 2012;Abrahams et al 2017), and the Crab Nebula, which did not pass the extension criteria threshold in Ackermann et al (2017c). Figure 3 shows the detected extension and extension upper limits for all the sources investigated in this analysis.…”
Section: Extension Catalogmentioning
confidence: 73%
“…We note that all of the new extended sources are found at low latitudes (     | | b 4 20 ), 69 implying potential Galactic origin. We found the sources were generally associated with either SNRs or SFRs, the two exceptions being the ρ Oph Cloud, which was originally discovered by COSB at γ-ray energies (Mayer-Hasselwander et al 1980) and was previously found as an extended object in γ-rays (Lande et al 2012;Abrahams et al 2017), and the Crab Nebula, which did not pass the extension criteria threshold in Ackermann et al (2017c). Figure 3 shows the detected extension and extension upper limits for all the sources investigated in this analysis.…”
Section: Extension Catalogmentioning
confidence: 73%
“…For example, since we expect that on scales larger than a protoplanetary disk, dust and gas should generally be well coupled and the dust-to-gas ratio should not vary much within gas of the same metallicity, it is natural to use observations of the dust to constrain the gas column density. Dust extinction measurements provide the cleanest measure of the column density (Lombardi & Alves, 2001;Kainulainen & Tan, 2013;Abrahams et al, 2017) but require one to have deep near IR and/or mid IR maps of the background stellar population in order to detect the extinction. If these are unavailable, the technique cannot be used.…”
Section: Probability Density Functionsmentioning
confidence: 99%
“…The total uncertainty including the statistical and systematic uncertainty is calculated with their root sum square, 11 and is shown as a red band in Fig. 5.…”
Section: A Results Of the Baseline Model And The Systematic Uncertaimentioning
confidence: 99%
“…The interaction of CRs with the interstellar gas will produce γ-ray photons. On one hand, these γ rays can be a useful tracer of total gas column density [7][8][9][10][11][12][13][14], since the γ rays are transparent to the interstellar medium (ISM) and also independent of the chemical and thermodynamic state. On the other hand, γ-ray observation provides a unique way to probe the Galactic CRs outside the solar system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation